2017
DOI: 10.1002/acp.3352
|View full text |Cite
|
Sign up to set email alerts
|

From Eyewitness to Academic Contexts: Examining the Effect of Misinformation in First and Second Languages

Abstract: The present study adapts the typical eyewitness misinformation paradigm into an academic context. Unbalanced English-Spanish bilinguals (N = 81) listened to a lecture in English (L1) or Spanish (L2), read notes in L1 or L2, and completed a forced-choice recognition test in the lecture language. Unlike prior studies with proficient bilinguals, unbalanced Englishdominant participants showed greater recognition memory accuracy for material presented in English only than did material presented in Spanish only. Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Educators sometimes accidently verbally contradict written information provided to their students prior to teaching sessions (e.g., lecture slide handouts), creating a situation where misinformation has been introduced, but where students may not immediately realize. Smith et al (2017) even demonstrated that misinformation can be introduced to students when they copy lecture notes from each other. Written notes about a lecture were given to a participant, with the notes containing deliberate mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…Educators sometimes accidently verbally contradict written information provided to their students prior to teaching sessions (e.g., lecture slide handouts), creating a situation where misinformation has been introduced, but where students may not immediately realize. Smith et al (2017) even demonstrated that misinformation can be introduced to students when they copy lecture notes from each other. Written notes about a lecture were given to a participant, with the notes containing deliberate mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Smith et al. (2017) found that participants who spoke English more fluently than Spanish (unbalanced bilinguals) remembered more information presented in English (lecture and lecture notes) compared to in Spanish. Lecture notes presented some misinformation.…”
Section: Forensic Interviews With L2 Speakersmentioning
confidence: 86%
“…When bilinguals are concerned, it also means that encoding can be different depending on the language they use at the moment. Yet, while episodic and autobiographical memory in bilinguals has been widely researched and differences in encoding and retrieval processes were observed (Boroditsky et al, 2009 ; Fausey and Boroditsky, 2011 ; Aydin and Ceci, 2013 ), there have been only a handful of studies investigating the suggestibility in bilinguals (Shaw et al, 1997 ; Smith et al, 2017 ; Calvillo and Mills, 2020 ). Although misinformation effect was present in all these cross-linguistic studies, the results regarding the influence of the language on the endorsement of false information show inconsistent findings, reporting no significant differences between the conditions (Shaw et al, 1997 ) or explaining the results in relation to the different levels of proficiency between the languages (Calvillo and Mills, 2020 ).…”
Section: Introductionmentioning
confidence: 99%